Dynamic Core Allocation: Enhancing Fault Tolerance and Energy Efficiency in Cloud Computing - Mongia, Vikas (International Journal of Computer Sciences and Engineering, 2023)
As the prevalence of cloud computing continues to surge, cloud computing entities face the formidable challenge of meeting coordinated Service Level Agreement (SLA) understandings, particularly in terms of stability and operational efficiency, all while achieving cost and energy efficiency. This paper introduces Shadow Replication, a novel adaptation to internal failure mechanisms for cloud computing that seamlessly addresses faults at scale, concurrently limiting energy consumption and reducing its impact on costs. Energy conservation is realized by establishing dynamic cores as opposed to static cores, achieved through the deployment of cloudlets. Essentially, equivalent cores are created, with core failure metrics considering memory capacity, energy, and power consumption. If any of these parameters exceed the threshold value, the core is flagged, and progress is maintained within a shadow, assigned one for each host. The workload of a failed core is transferred to the next core within another virtual machine (VM). In the event of all cores within a VM failing, VM migration is executed. Results obtained through the proposed system exhibit improvements in indexed energy consumption, latency, cost, and fault rate.